Influence of Chamber Geometrical Parameters on Suppressing Explosion Propagation. (31st August 2021) - Yan, Zhuo; Guo, Shengli; Yuan, Shujie; Mu, Chaomin
Abstract : In this article, the effect of a chamber's geometrical parameters on suppressing gas explosion propagation was studied. Three rectangular chambers were used in the study, with a constant length of 0.5 m, a constant height of 0.2 m, and a variable width of 0.3 m, 0.5 m, and 0.8 m; each chamber was installed in a pipeline system for experimental research. The experimental results showed that when the chamber length and height were fixed at 0.5 m and 0.2 m, respectively, the suppression effect of the chamber on the explosion shockwave improves with the increase in the chamber width; when the chamber width increases to 0.8 m, the chamber has suppressive effect on explosion shockwave propagation. It was also found that the suppression effect of the chambers on the explosion flame improves with the increase in the chamber width; when the width of the chamber is 0.5 m, the chamber effectively suppresses explosion flames. Based on the experimental results, a numerical model was established to simulate the suppression effect of five types of chambers with a length, width, and height of 0.5 m × 0.3 m × 0.2 m, 0.3 m × 0.5 m × 0.2 m, 0.5 m × 0.5 m × 0.2 m, 0.5 m × 0.8 m × 0.2 m, and 0.8 m × 0.5 m × 0.2 m, respectively. The numerical simulation results indicated that when the chamber length and height are constant at 0.5 m and 0.2 m, respectively, the suppressive effect of the chamber on the shockwave improves as the chamber width increases; when the chamber width increases to 0.8 m, the shockwave overpressure at the chamber outlet is attenuated by 10.61%, indicating that the chamber suppresses the propagation of explosion shockwave, which is consistent with the experimental results obtained in the study. It was also found that when the chamber width and height were constant at 0.5 m and 0.2 m, respectively, as the chamber length increases, the overpressure increases first and then weakens. When the chamber length increases to 0.8 m, the overpressure at the chamber outlet is attenuated by −14.16%, indicating that the chamber is not able to suppress the propagation of explosion shockwave. Finally, a numerical simulation of the propagation process of a methane-air mixture and explosion flames in different chambers was performed to analyse the effect of chamber geometrical parameters on explosion suppression effect.